Fluorescent Tobacco mosaic virus-Derived Bio-Nanoparticles for Intravital Two-Photon Imaging - Niehl, Annette; Appaix, Florence; Boscá, Sonia; van der Sanden, Boudewijn; Nicoud, Jean-François; Bolze, Frédéric; Heinlein, Manfred (Frontiers in Plant Science, 2016)
Multi-photon intravital imaging has become a powerful tool to investigate the healthy and diseased brain vasculature in living animals. Although agents for multi-photon fluorescence microscopy of the microvasculature are available, issues related to stability, bioavailability, toxicity, cost or chemical adaptability remain to be solved. In particular, there is a need for highly fluorescent dyes linked to particles that do not cross the blood brain barrier (BBB) in brain diseases like tumor or stroke to estimate the functional blood supply. Plant virus particles possess a number of distinct advantages over other particles, the most important being the multi-valency of chemically addressable sites on the particle surface. This multi-valency, together with biological compatibility and inert nature, makes plant viruses ideal carriers for in vivo imaging agents. Here, we show that the well-known Tobacco mosaic virus is a suitable nanocarrier for two-photon dyes and for intravital imaging of the mouse brain vasculature.